The effect of fire history on soil nutrients and soil organic carbon in a semi-arid savanna woodland, central Namibia. Issue 1 (2nd January 2019) - Nghalipo, Elise; Joubert, Dave; Throop, Heather; Groengroeft, Alexander
Abstract : Fire is an integral part of savanna ecosystems that has shaped these systems since the Miocene. Substantial uncertainty about fire effects in semi-arid ecosystems exists. Fire may affect ecosystem productivity directly through nutrient volatilisation, increased mineralisation and altering organic matter quantity, and indirectly through altering vegetation structure. We explored the effects of fire history and vegetation patch types (tree canopy vs inter-canopy) on soil nutrients and soil organic carbon (SOC) in a semi-arid ecosystem. We collected soil samples along transects in four treatments with different fire histories (1 to 24 years since the last burn). In the statistical analyses, tree canopy and inter-canopy samples along transects were differentiated. Fire showed an inconsistent effect on soil nutrients and SOC. There was a short-term negative influence on total nitrogen, whereas phosphorus, potassium and magnesium increased in the 1-year treatment. Sodium consistently decreased with increasing time since the last burn, whereas SOC and calcium were not affected. Calcium and magnesium were significantly higher under canopy relative to inter-canopy patches. There was no significant interactive effect between fire history and vegetation patch type on soil nutrients and SOC. Management decisions regarding fire within the frequency experienced in this system appear not to necessitate concern regarding soil resource impacts.